2016
DOI: 10.1002/14651858.cd009832.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Zinc supplementation for tinnitus

Abstract: Background Tinnitus is the perception of sound without external acoustic stimuli. Patients with severe tinnitus may have physical and psychological complaints and their tinnitus can cause deterioration in their quality of life. At present no specific therapy for tinnitus has been found to be satisfactory in all patients. In recent decades, a number of reports have suggested that oral zinc supplementation may be effective in the management of tinnitus. Since zinc has a role in cochlear physiology and in the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 73 publications
0
32
0
2
Order By: Relevance
“…Antioxidant supplementation studies in tinnitus are limited. Moreover, in most of them a monotherapy treatment approach has been proposed such as zinc [16,55,56], with no benefit in tinnitus. On the contrary, our hypothesis was that an antioxidant combination might be more effective compared with single nutrients, since various antioxidants have a synergistic/complementary activity [57].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant supplementation studies in tinnitus are limited. Moreover, in most of them a monotherapy treatment approach has been proposed such as zinc [16,55,56], with no benefit in tinnitus. On the contrary, our hypothesis was that an antioxidant combination might be more effective compared with single nutrients, since various antioxidants have a synergistic/complementary activity [57].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of zinc in patients with tinnitus is controversial among several reports [12] , [13] , [14] , [15] . In recent studies, zinc was not effective in treating adults with tinnitus [16] ; however, other authors identified patients with different etiology who may benefit from zinc supplementation [17] . Different access to tinnitus patients could be required according to audiometric shape [18] .…”
mentioning
confidence: 99%
“…According to Cochrane reviews, supplementation with ginkgo biloba or zinc does not relieve tinnitus symptoms and is no more effective than placebo (adverse effects such as gastrointestinal disturbances, headache or allergic reactions may occur). 25,26 Randomised, double-blinded, placebocontrolled trials also failed to show any effects on the use of antioxidant agents for tinnitus management (eg vitamins C and E, β-carotene, α-lipoic acid). 27,28 Nonetheless, after medications (45%) and hearing aids (9%), dietary supplements (8%) are one of the most widely discussed interventions in tinnitus management with physicians, as shown by a cross-sectional analysis of the representative 2007 National Health Interview Survey.…”
Section: Use Of Dietary Supplementsmentioning
confidence: 99%